Effect of Antifungal Hydroxypropyl Methylcellulose-Lipid Edible Composite Coatings on Penicillium Decay Development and Postharvest Quality of Cold-Stored "Ortanique" Mandarins - Valencia-Chamorro, Silvia A.; Pérez-Gago, María B.; Del-Río, Miguel A.; Palou, Lluís (2017)
Edible composite coatings based on hydroxypropyl methylcellulose (HPMC), hydrophobic components (beeswax and shellac), and food preservatives with antifungal properties were evaluated on "Ortanique" mandarins during long-term cold storage. Selected food preservatives included potassium sorbate (PS), sodium benzoate (SB), sodium propionate (SP), and their mixtures. Intact mandarins or mandarins artificially inoculated with the pathogens Penicillium digitatum and Penicillium italicum, the causal agents of citrus postharvest green (GM) and blue (BM) molds, respectively, were coated and stored up to 8 wk at 5 degrees C + 1 wk of shelf-life at 20 degrees C. HPMC-lipid coatings containing food preservatives controlled better GM than BM on Ortanique mandarins. SB- and SB + SP-based coatings reduced the incidence of GM by about 35% after 4 wk at 5 degrees C. Among all coatings, only the SB-based coating reduced the incidence of GM (about 16%) after 6 wk at 5 degrees C. All coatings significantly reduced disease severity of both GM and BM after 6 wk at 5 degrees C. Analytical and sensory fruit quality was evaluated on intact mandarins. All coatings, especially the SB + SP-based coatings, were effective to control weight loss and maintain the firmness of coated mandarins. Internal gas concentration, juice ethanol and acetaldehyde content, sensory flavor, off-flavor, and fruit appearance were not adversely affected by the application of the antifungal coatings. Further studies should focus on the modification of some physical characteristics of the coatings to improve the gloss and visual aspect of treated mandarins.